How Students Deal With Password Security: Case Study of Nalut University Students - Al-Jerbie, Saida Issa; Jernaz, Riad Suliman; Askar, Ekram; Benhamed, Doa; Kamis, Zahra; OunAllah, Salsabill (European Scientific Journal, ESJ, 2024)
University students are the largest segment of society that uses modern technology, represented by computers and smart phones, and to ensure the security and integrity of information, students must consider the most common protection methods for conducting the electronic authentication process. This research seeks to evaluate the extent of awareness of Nalut University students about password policies. The size of the study sample was (539) students, and the average age of the sample was (between 18 and 20 years) out of 2177 students. The questionnaire was analyzed using the statistical analysis program SPSS, version (26). The results of the study showed that the level of awareness among Nalut University students was low, as their percentage was 49.8%. It was found that there is a relationship between gender and password policy among university students, where the p value was = 0.01.